2016
DOI: 10.1089/neu.2015.4068
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Previous Physical Training on Redox Signaling after Traumatic Brain Injury in Rats: A Behavioral and Neurochemical Approach

Abstract: Throughout the world, traumatic brain injury (TBI) is one of the major causes of disability, which can include deficits in motor function and memory, as well as acquired epilepsy. Although some studies have shown the beneficial effects of physical exercise after TBI, the prophylactic effects are poorly understood. In the current study, we demonstrated that TBI induced by fluid percussion injury (FPI) in adult male Wistar rats caused early motor impairment (24 h), learning deficit (15 days), spontaneous epilept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 89 publications
3
7
0
Order By: Relevance
“…In the present study, we have demonstrated that high levels of circulating cytokines elicited by FPI affect the brain response to injury and contribute to BBB opening, neurtrophil infiltration and Na + ,K + -ATPase activity inhibition. These results are in line with previous findings from our group suggesting that a single episode of FPI affects the inflammatory status of the brain (Mota et al 2012), impairs performance in spatial learning and induces cell loss in the dentate gyrus hilus (Lima et al 2008;da Silva Fiorin et al 2016). However, the understanding of secondary damage post-injury is essential for establishing scientific-based rehabilitation following TBI.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, we have demonstrated that high levels of circulating cytokines elicited by FPI affect the brain response to injury and contribute to BBB opening, neurtrophil infiltration and Na + ,K + -ATPase activity inhibition. These results are in line with previous findings from our group suggesting that a single episode of FPI affects the inflammatory status of the brain (Mota et al 2012), impairs performance in spatial learning and induces cell loss in the dentate gyrus hilus (Lima et al 2008;da Silva Fiorin et al 2016). However, the understanding of secondary damage post-injury is essential for establishing scientific-based rehabilitation following TBI.…”
Section: Discussionsupporting
confidence: 91%
“…Motor impairment is a common TBI disability (Mota et al 2012;da Silva Fiorin et al 2016). Using the composite neuroscore, we demonstrated that FPI-induced motor impairment (F 1,20 = 10.58; P < 0.05) ( Fig.…”
Section: Exercise Training Protects Against Tbi-induced Motor Impairmmentioning
confidence: 82%
See 2 more Smart Citations
“…Gene expression of catalytic subunits of Na + , K + ‐ATPase was not altered in amygdala. Moreover, as demonstrated by da Silva Fiorin et al (2016), previous exercise may have a preventive therapeutic potential on the redox signaling and activity of Na + , K + ‐ATPase in model of traumatic brain injury, as well as in experimental depression as seen in our study.…”
Section: Discussionsupporting
confidence: 73%